Chemical Composition of Essential Oils of Centella asiatica L Urban from Different Habitats of Nepal - Devkota, Anjana (International Journal of Pharmaceutical & Biological Archive, 2013)
Chemical Composition of Essential Oils of Centella asiatica L Urban from Different Habitats of Nepal